Socialization and Training of The Use of Inventory Applications for Optimization of Goods Inventory (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
This service is entitled Socialization and Training on the Use of Inventory Applications for Optimizing Goods Inventory. The problems faced by partners include; First, (1) There is no socialization and training on the Inventory application, (2) Difficulty in making accurate customer demand forecasts. The output targets in this program are (1) application of services carried out by providing socialization and training, (2) Providing knowledge of proper and accurate inventory management. The service program is carried out in 2 forms; First, (1) socialization and training on the use of inventory applications. In using the inventory application, the training was carried out in 4 meetings. Every meeting there are training activities and socialization of the use of inventory applications to partners. Second, the design of the Nyong Group sales transaction inventory application. Second, activities and knowledge about optimizing inventory. These training sessions are conducted with partners and employees. The implementation of this program is designed in four stages of activity, namely: (1) Coordination and preparation stage (2) Training stage (3) Science and technology implementation stage (4) Evaluation & Mentoring Stage.